If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x + 9 = 8 Reorder the terms: 9 + 2x + 3x = 8 Combine like terms: 2x + 3x = 5x 9 + 5x = 8 Solving 9 + 5x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = 8 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 8 + -9 5x = 8 + -9 Combine like terms: 8 + -9 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| 6x^2+28x+26=0 | | 10=-12-e | | (7x+13)+(7x-2)= | | -2(y-3)=y+4s | | 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 |